Beyond Black Celebrity and Race in Obama's America - Cashmore, Ellis (Bloomsbury Academic, 2012)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Beyond Black is Ellis Cashmore's compelling appraisal of the impact of black celebrities on the cultural landscape of contemporary America. In recent years a new variety of African American celebrity has emerged: acquisitive, ambitious, flamboyantly successful and individualistic - more interested in channelling their energy into career development than into the political struggles that animated some of their predecessors. Bill Cosby and Oprah Winfrey were early examples; current A-listers include Beyoncé and Tiger Woods. The most valuable product these celebrities sell, according to Cashmore, is a particular conception of America: as a nation where racism has been - if not banished - rendered insignificant. Jargon-free but with scholarly attention to theory, evidence and logic, this is a riveting account of contemporary American society, from the minstrel shows of the nineteenth century, through the Hollywood film industry of the 1930s, to today's hip-hop culture.